Profile of The Needs for Digital-Based Listening Learning Media in Higher Education : Responding to The Challenges of 21st Century Learning - Septyanti, Elvrin; Zulhafizh, Zulhafizh; Mustika, Tria Putri; Asnawi, Asnawi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to identify the required listening comprehension learning media for lecturers and students, and assess their suitability for today's digital era in higher education. The research employed a descriptive qualitative approach with a cross-sectional survey design. The informants in this research involved students from Indonesian Language and Literature Education from Riau University, Riau Islamic University, and Sultan Syarif Kasim Riau State Islamic University who took Listening classes in the Indonesian Language and Literature Education study program. Data were collected through open questionnaires distributed to participants using Google Forms comprising 30 questions. The data analysis involved various stages, including data recording, accuracy verification, database structure development, calculating data acquisition percentages based on classification, data analysis, and data summarization. The results indicated that the needs for digital-based listening comprehension learning media were determined based on four indicators: content, language, graphics, and learning media aspects. The envisioned learning media should take the form of an application with comprehensive and meaningful teaching materials, including ebooks, integrating textual, visual, and video content to reflect the local wisdom of Riau culture, thereby fostering students' critical thinking, reasoning, and imagination skills.